Transcriptional signatures of invasiveness in Meloidogyne incognita populations from sub-Saharan Africa. Issue 11 (October 2019) - Cox, Deborah; Reilly, Brian; Warnock, Neil D.; Dyer, Steven; Sturrock, Matthew; Cortada, Laura; Coyne, Danny; Maule, Aaron G.; Dalzell, Johnathan J.
Graphical abstract: Highlights: Populations of Meloidogyne incognita vary significantly in their ability to invade tomato seedlings. This variation correlates with a range of gene expression markers (GEMs) that span protein-coding and non-coding genes. Neuropeptide, GPCR, ion channel and cell wall degrading enzyme genes are identified as GEMs of M. incognita invasion. Two microRNA genes correlate with invasiveness, and are predicted to target genes of relevance to nematode behaviour. We identify numerous microRNA-mRNA interactions that indicate biologically relevant mRNA decay patterns. Abstract: Meloidogyne incognita is an economically important plant parasitic nematode. Here we demonstrate substantial variation in the invasiveness of four M. incognita populations relative to tomato. Infective (J2) stage transcriptomes reveal significant variation in the expression of protein-coding and non-coding RNAs between populations. We identify 33 gene expression markers that correlate with invasiveness, and which map to genes with predicted roles in host finding and invasion, including neuropeptides, ion channels, G Protein-Coupled Receptors, cell wall-degrading enzymes and microRNAs. These data demonstrate a surprising diversity in microRNA complements between populations, and identify gene expression markers for invasiveness of M. incognita, to our knowledge for the first time.